Phytochemicals Approach for Developing Cancer Immunotherapeutics - Yin, Shu-Yi; Yang, Ning-Sun; Lin, Tien-Jen (Frontiers in Pharmacology, 2017)
Phytochemicals or their derived compounds are being increasingly recognized as potentially potent complementary treatments for cancer. Among them, some phytochemicals are being actively evaluated for use as adjuvants in anticancer therapies. For instance, shikonin and hypericin were found to induce immunogenic cell death (ICD) of specific cancer cells, and this effect was able to further activate the recognition activity of tumor cells by the host immune system. On the other hand, some derivatives of phytochemicals, such as dihydrobenzofuran lignan (Q2-3) have been found to induce the secretion of an endogenous anticancer factor, namely IL-25, from non-malignant cells. These findings suggest that phytochemicals or their derivatives confer a spectrum of different pharmacological activities, which contrasts with the current cytotoxic anticancer drugs commonly used in clinics. In this review, we have collected together pertinent information from recent studies about the biochemical and cellular mechanisms through which specific phytochemicals regulate target immune systems in defined tumor microenvironments. We have further highlighted the potential application of these immunotherapeutic modifiers in cell-based cancer vaccine systems. This knowledge provides useful technological support and knowhow for future applications of phytochemicals in cancer immunotherapy.